Pengaruh Retrun on Assets, Debt to Assets Ratio, dan Total Aktiva terhadap Audit Delay : Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar pada BEI Periode 2020-2024 - Ayu Juniarti; Suryani Suryani (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to examine the effect of Return on Assets (ROA), Debt to Assets Ratio (DAR), and Total Assets on Audit Delay in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Audit Delay is defined as the time interval between the end of the fiscal year and the issuance date of audited financial statements by independent auditors. The timeliness of financial reporting is a crucial element for stakeholders in evaluating company performance, enhancing transparency, and supporting decision-making processes. Therefore, understanding the factors that influence audit delay is important in the context of both regulatory compliance and corporate governance. This research adopts a quantitative methodology using multiple linear regression analysis. The data used are secondary data obtained from annual financial reports published and accessible through the official IDX website. The study sample consists of 33 companies, resulting in 165 observations. After conducting outlier analysis, the final dataset comprised 83 observations. Data analysis was carried out using the Statistical Package for the Social Sciences (SPSS) Version 22. The results show that Return on Assets and Total Assets do not have a significant effect on Audit Delay. This indicates that profitability and company size are not the main determinants of audit timeliness in this sector. However, the Debt to Assets Ratio was found to have a relatively positive effect on Audit Delay. This finding suggests that companies with higher leverage tend to be audited more quickly, possibly because auditors and stakeholders pay greater attention to firms with higher financial risk. Thus, a company’s capital structure plays an important role in influencing the timeliness of audit completion.